Clinical characteristics of patients with severe sepsis and septic shock in relation to bacterial virulence of beta‐hemolytic Streptococcus and Streptococcus pneumoniae. Issue 1 (31st May 2020) - Hifumi, Toru; Fujishima, Seitaro; Ubukata, Kimiko; Hagiwara, Akiyoshi; Abe, Toshikazu; Ogura, Hiroshi; Shiraishi, Atsushi; Kushimoto, Shigeki; Saitoh, Daizoh; Mayumi, Toshihiko; Ikeda, Hiroto; Ueyama, Masashi; et al.
Abstract : Aim: Combined detailed analysis of patient characteristics and treatment as well as bacterial virulence factors, which all play a central role in the cause of infections leading to severe illness, has not been reported. We aimed to describe the patient characteristics (Charlson comorbidity index [CCI]), treatment (3‐h bundle), and outcomes in relation to bacterial virulence of Streptococcus pneumoniae and beta‐hemolytic Streptococcus (BHS). Methods: This sepsis primary study is part of the larger Focused Outcomes Research in Emergency Care in Acute Respiratory Distress Syndrome, Sepsis and Trauma (FORECAST) study, a multicenter, prospective cohort study. We included patients diagnosed with S. pneumoniae and BHS sepsis and examined virulence, defining the high‐virulence factor as follows: S. pneumoniae serotype 3, 31, 11A, 35F, and 17F; Streptococcus pyogenes, emm 1 ; Streptococcus agalactiae, III; and Streptococcus dysgalactiae ssp. equisimilis, emm typing pattern stG 6792 . Included patients were divided into high and normal categories based on the virulence factor. Results: Of 1, 184 sepsis patients enrolled in the Japanese Association for Acute Medicine's FORECAST study, 62 were included in the current study (29 cases with S. pneumoniae sepsis and 33 with BHS). The CCI and completion of a 3‐h bundle did not differ between normal and high virulence groups. Risk of 28‐day mortality was significantly higher for high‐virulence compared to normal‐virulence when adjusted for CCI and completion of a 3‐h bundle (Cox proportional hazards regression analysis, hazard ratio 3.848; 95% confidence interval, 1.108–13.370; P = 0.034). Conclusion: The risk of 28‐day mortality was significantly higher for patients with high‐virulence compared to normal‐virulence bacteria. Abstract : The risk of 28‐day mortality was significantly higher for patients infected with high‐virulence compared to normal‐virulence bacteria. Charlson comorbidity index and completion of a 3‐h bundle did not differ between normal‐ and high‐virulence groups.